Spherical Element Bulking Mechanisms for Modeling Blasting Induced Rock Motion (64700483-5a3c-4893-9e17-9d150ed129be) - Dale S. Preece; Lee M. Taylor (International Society of Explosives Engineers, 1990)
Accurate computer prediction of the muck pile produced by a conventional blast requires modeling of the physics that occurs during the rock motion phase of a blast. The ability to predict the motion and the subsequent muck pile can have a significant economic impact on the mining industry.